(untitled) (Journal of Pure & Applied Sciences, 2023)
In this study, optimal characteristics for duplex stainless steels (2507DSS) are attained when austenite and ferrite are present in roughly equal amounts in the microstructure. Therefore, the purpose of this study is to compare how different metal inert gas (MIG) and laser welding (LBW) parameters affect the weld characters of joints that are butt welded joints of duplex stainless steel plate with thickness of 8mm, the speed is constant and changing beam power, with argon shielding gas. Conventional MIG welding parameters are ranges; current, voltage are constant with changing speed and using gas mixture Ar and CO2 with a filler metal, and a single V groove. Investigation of welded joints has been carried out using different methods visual inspection, optical micro structure, hardness measurements, energy dispersive X-ray (EDX) microanalysis and tensile test. The results achieved in this investigation disclosed that welding parameters obtaining satisfactory properties of welded joint; no visible welding flaws, porosity and incompetent penetration. The fusion zone’s grain size is finer in LB than MIG welding. EDX microscopic analysis reveals a slightly different structure in MIG and LB welds of BM microstructure, with filler altering Fe element and C-carbone content, causing brittleness due to ferrite content. The hardness results showed that no appreciable differences between MIG and LB in the welding bool area zone were equalled (265- 289Hv) respectively. Tensile strength and ductility increased with MIG and LBW in HAZ, at the same time laser welded specimens showing the highest ductility and strength.